2012
DOI: 10.1117/12.915703
|View full text |Cite
|
Sign up to set email alerts
|

Novel DEA with organically modified silicone elastomer for permittivity enhancement

Abstract: Dielectric elastomer actuators (DEA) based on an organically modified silicone elastomer are introduced. The elastomer carries fluorinated sidegroups in the polysiloxane molecular chain and is synthesized from precursors which all are fluorinated. A fluorinated silicone oil is added in consecutive concentration steps as a softening agent. The electric properties of the modified silicone elastomers in terms of the permittivity, specific conductivity and electric breakdown field strength were investigated and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Commercial fluorosilicones were investigated early on by Pelrine et al but were shown to exhibit high leakage currents . Later, Böse et al prepared a home‐made system using trifluoropropyl‐functional divinylpolydimethylsiloxane, cross‐linked into an elastomer and mixed with fluorinated silicone oil, to create very soft silicone elastomers ( Y = 0.07 MPa at 45 wt% oil) with enhanced dielectric permittivity of up to ε' = 5.4. The actuation strain was improved by a factor of five using 40 or 45 wt% fluorinated silicone oil, though the leakage current was not stated.…”
Section: Investigated Silicone Materials For Dielectric Elastomersmentioning
confidence: 99%
“…Commercial fluorosilicones were investigated early on by Pelrine et al but were shown to exhibit high leakage currents . Later, Böse et al prepared a home‐made system using trifluoropropyl‐functional divinylpolydimethylsiloxane, cross‐linked into an elastomer and mixed with fluorinated silicone oil, to create very soft silicone elastomers ( Y = 0.07 MPa at 45 wt% oil) with enhanced dielectric permittivity of up to ε' = 5.4. The actuation strain was improved by a factor of five using 40 or 45 wt% fluorinated silicone oil, though the leakage current was not stated.…”
Section: Investigated Silicone Materials For Dielectric Elastomersmentioning
confidence: 99%
“…Along the same lines, Böse et al used the vinyl end‐functionalized polysiloxane with trifluoropropyl side‐groups, P5 (Scheme d) and formed an interconnected network with PDMS using a hydrosilylation reaction. A material containing about 45 wt% of polar polysiloxane showed a ε′ = 5.5, a strain at break as high as 400%, and a maximum actuation strain of 7.5% at 14 V µm −1 . A further increase in the polar fraction of the elastomer resulted in difficult to handle, very soft films.…”
Section: Synthesis and Actuation Of High Dielectric Permittivity Elasmentioning
confidence: 99%
“…Blending silicones with conductive or highly dielectric polymeric fillers affords an alternative approach to increasing permittivity . For example, Carpi and coworkers blended polydimethylsiloxane rubber with 1–6 wt% of conductive poly(3‐hexylthiophene) (PHT) .…”
Section: Dielectric Elastomer Actuatorsmentioning
confidence: 99%